Analisis Pengaruh Promosi Terhadap Penjualan Mobil Di Tunas Toyota Cilegon - Imam Imadussalam; Budi Astuti (EBISMAN eBisnis Manajemen, 2023)
This research aims to analyze the impact of promotions on sales at Tunas Toyota Cilegon by examining promotions at exhibitions, brochures, and social media. The type of research used in this study is quantitative research. The research method used in this study is multiple linear regression analysis. The analytical tool used is factor analysis using IBM SPSS Version 25.0 as a supporting tool. The research was conducted at Tunas Toyota Cilegon by processing sales data for the year 2022. Data collection techniques used include interviews, observations, and documentation. The research results indicate that using exhibition promotions and social media promotions has a significant positive impact on sales at Tunas Toyota Cilegon. However, brochure promotions have a significant negative impact on sales at Tunas Toyota Cilegon.